The problem of the language of the Liturgy and national identity in the service of Metropolitan Vasyl Lypkivskyi - archpriest Sergei Ursta; Evgeny Nikolsky (Волинський благовісник, 2019)
The article analyzes the situation associated with the introduction of the Ukrainian language in worship and other aspects of building a national Church. In this context, analyses the specific moments with the pastoral work of Metropolitan Basil (Lipkivsky). It is noted that 70 years have passed since the martyrdom of Metropolitan Basil. During this time, Ukraine became an independent country, but the problems for the solution of which Vasily lipkovsky was martyred, and remain deadlocked. Thus, the Orthodox of Ukraine still lack unity – part of our Orthodoxy is still connected (like shackles) with the Imperial Church, the Church of another state! And the end of this abnormal situation is very difficult to predict.In the time of Vasily lipkivsky, the Russian Orthodox Church and the Bolshevik government stood in the way of the UAOC's approval. The bishops and supporters of the Russian Orthodox Church noted "necrosociety" Ukrainian autocephaly, the Bolsheviks – it "kontrrevoljucionnoj". The Metropolitan rejected both arguments. In particular, in discussions on the Church system, he noted that the Russian Orthodox Church does not accidentally draw attention to the Church canons. However, in the circumstances of General significant changes in life, instead of the monarchicalecclesiastical system, it is necessary to establish a people's right system. It would seem that the Bolshevik authorities did not perceive the Autocephalous Church for fundamentally different reasons than the ROC. In fact, there was a deeply common ground that United the Bolsheviks and Russian churchmen in their irreconcilable attitude to the UAOC. Neodnorodnosti autocephalists scared as the Russian Orthodox Church and the Bolsheviks. The Communists could not allow the existence of the UAOC, because it was a spiritual organization beyond the control of the authorities. It was unacceptable for them that Ukrainians should start to organize themselves on a spiritual basis and remember that they are a separate ethnic community from the Russians with their history, culture, customs, Church, and that they should finally address God in their native language.